2011
DOI: 10.1097/mot.0b013e32834a94cf
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary liver transplantation in children

Abstract: Auxiliary liver transplantation should be considered for the treatment of children with acute liver failure satisfying current criteria for liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…1 The standard technique of arterial reconstruction in deceased donor APOLT uses a cadaveric iliac artery conduit, which brings inflow from the supraceliac aorta, infrarenal aorta, splenic artery, or gastroduodenal artery. 1,[10][11][12] In the setting of adult living donor APOLT, a direct anastomosis between the donor's right hepatic artery and the recipient's right hepatic artery is feasible. However, in pediatric living donor APOLT, a discrepancy between the donor and recipient arteries is common.…”
Section: Reportmentioning
confidence: 99%
“…1 The standard technique of arterial reconstruction in deceased donor APOLT uses a cadaveric iliac artery conduit, which brings inflow from the supraceliac aorta, infrarenal aorta, splenic artery, or gastroduodenal artery. 1,[10][11][12] In the setting of adult living donor APOLT, a direct anastomosis between the donor's right hepatic artery and the recipient's right hepatic artery is feasible. However, in pediatric living donor APOLT, a discrepancy between the donor and recipient arteries is common.…”
Section: Reportmentioning
confidence: 99%
“…Another less extended indication for APOLT are metabolic liver diseases, mainly in children, where the rationale for LT is not to withdraw immunosuppression long term but to provide enough liver mass to replace the missing enzymatic function, with the advantage that if the graft fails the native liver is still functional to act as security net30 and also for future gene therapy 31. The main indications have been Crigler Najjar type 1 and urea cycle disorders 32.…”
Section: What Can Be Done To Achieve An Ideal Outcome?mentioning
confidence: 99%
“…In the King's College Hospital series of 128 liver transplants in children with ALF, 20 received auxiliary allografts and 14 of 17 survivors had native liver regeneration. [22] Kato et al also reported six cases in children with 100% survival, but only one patient had been weaned from immunosuppression at the time of reporting. [23] Conclusion ALF in children is as challenging as any field of clinical medicine.…”
Section: Transplant Work-up and Organ Availabilitymentioning
confidence: 99%
“…The history of this procedure stretches back to animal experiments in the 1950s and human experience starting in 1964, although success was elusive until the 1980s. [22] The majority of recipients of an auxiliary liver graft can be expected to have regeneration of their native liver, and it has been estimated that twothirds of longterm survivors will eventually be free of immunosuppression. Once native liver regeneration has been assured by biopsy, computed tomography volumetry and hepatic scintigraphy, a patient can gradually be weaned off immunosuppression and the graft will involute.…”
Section: Transplant Work-up and Organ Availabilitymentioning
confidence: 99%